S83 An Economic Evaluation Of Domiciliary Non-invasive Ventilation (niv) In Patients With End-stage Copd In The Uk. (10th November 2014) - Blissett, D; Jowett, S; Turner, A; Moore, D; Dretzke, J; Mukherjee, R; Dave, C
Abstract : This abstract summarises independent research funded by the National Institute for Health Research (NIHR) under its HTA Programme (Ref 11/27/01). The views expressed are those of the author (s) and not necessarily those of the NHS, the NIHR or the Department of Health. Background: NIV is an established treatment for the management of acute exacerbation of COPD but less is known about the effectiveness of NIV in the home setting. Many clinicians consider domiciliary NIV to be cost-effective in patients that have experienced three or more exacerbations however no economic evaluations, using decision modelling have been conducted. Methods: The findings of a systematic clinical review of the clinical effectiveness of domiciliary NIV in COPD were applied in a Markov model, to estimate cost-effectiveness, from a UK perspective, when compared to usual care. Outcomes were measured in Quality Adjust Life Years (QALYs). Two end-stage COPD populations were considered; patients that were stable for at least twelve weeks (stable population) and those recently discharged for exacerbation (post-admission population). Given the uncertainty around the effect of domiciliary NIV on admissions and mortality in both populations, extensive sensitivity analysis was conducted to quantify and likelihood of NIV being cost-effective at a thresholds of £30, 000 per QALY and the model's sensitivity to key parameters. Results: This model indicated that domiciliary NIV is unlikely to be cost-effective in stable populations but is more likely to be cost-effective post-admission. However, there was considerable uncertainty around the results for both populations. The model was most sensitive to changes in the risk ratio for admission and the duration of the effect but was also sensitive to changes in baseline risk of admissions. Conclusion: This model indicates that domiciliary NIV is unlikely to be cost-effective in stable patients but maybe cost-effective in patients with a history of admissions. This speculative economic model describes the uncertainty around these conclusions.